Assessment of particulate matter and ammonia emission concentrations and respective plume profiles from a commercial poultry house. (July 2018) - Yao, Qi; Yang, Zijiang; Li, Hong; Buser, Michael D.; Wanjura, John D.; Downey, Peter M.; Zhang, Chen; Craige, Collin; Torrents, Alba; McConnell, Laura L.; Holt, Gregory A.; Hapeman, Cathleen J.
Abstract: Poultry-emitted air pollutants, including particulate matter (PM) and ammonia, have raised concerns due to potential negative effects on human health and the environment. However, developing and optimizing remediation technologies requires a better understanding of air pollutant concentrations, the emission plumes, and the relationships between the pollutants. Therefore, we conducted ten field experiments to characterize PM (total suspended particulate [TSP], particulate matter less than 10 μm in aerodynamic diameter [PM10 ], and particulate matter less than 2.5 μm in aerodynamic diameter [PM2.5 ]) and ammonia emission-concentration profiles from a typical commercial poultry house. The emission factors of the poultry house, which were calculated using the concentrations and fan speed, were 0.66 (0.29–0.99) g NH3 -N bird −1 d −1 for ammonia, 52 (44–168) g d −1 AU −1 (AU = animal unit = 500 kg) for TSP, 3.48 (1.16–9.03) g d −1 AU −1 for PM10, and 0.07 (0.00–0.36) g d −1 AU −1 for PM2.5 . PM and ammonia emission concentrations decreased as distance from the fan increased. Although emission concentrations were similar in the daytime and nighttime, diurnal and nocturnal plume shapes were different due to the increased stability of the atmosphere at night. Particle size distribution analysis revealed that, at a given height, the percentage of PM10 and PM2.5 was consistent throughout the plume, indicating that the larger particles were not settling out of the airstream faster than the smaller particles. Overall, the direction of the measured air pollutant emission plumes was dominated by the tunnel fan ventilation airflow rate and direction instead of the ambient wind speed and direction. This is important because currently-available air dispersion models use ambient or modeled wind speed and direction as input parameters. Thus, results will be useful in evaluating dispersion models for ground-level, horizontally-released, point sources and in developing effective pollutant remediation strategies for emissions. Graphical abstract: Vertical and horizontal measured PM emission plumes from a commercial poultry house.Image 1 Highlights: Pollutant plume direction was dominated by the fan instead of the ambient wind. Measured PM plumes were longer and wider than NH3 during calmer wind conditions. Molecular diffusion influenced total ammonia diffusion in calm periods. Particle size distribution did not change with distance from the tunnel fan. Ammonia and PM10 concentrations were moderately correlated. Abstract : Plume direction was dominated by the fan not ambient wind; PM plumes were longer/wider than NH3 in calmer winds; particle size distribution did not change with distance from the fan (<50 m).